THE YOUTH MOVEMENT, ROCHEDALE, AND THE COUNSELLOR - Engright, Robert (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1972)
Sociologists, psychiatrists, psychologists and academics in many disciplines related to the study of human relations are having a field day commenting upon the condition and direction toward which our society is presently moving. One social phenomenon that is of particular interest to us as counsellors and educators is the movement afoot among our youth. This movement is characterized by feelings of uncertainty, instability, and a lack of comfort when considering the past and the present as a reference for future action. It is a surging whirlpool into which many of our young people have plunged in an attempt at self-discovery. Sorne are reaching calmer waters. Sorne are caught in the center. Some have drowned. This movement and the attitudes that it generates and nurtures have profound implications for the theory and practice of counselling. We are surrounded by young people who are looking to us for direction. How we help them is indeed crucial. For the past two years, the writer has given considerable thought to deciphering and unweaving "what it is all about." At times the search has resulted in information or experiences which have led to a better understanding of our young people. At other times I have had no recourse but to retreat into the uncertainty of my thoughts endeavouring to retrieve a missing link. Initially, I would like to share sorne of the thoughts I have had as a result of a particular experience which was shared with two other counsellors. I will then consider its implications for counselling.